Inhibition of Steel Corrosion Rate in Sulfuric Acid Solution with Various Concentrations Using Soursop (Annona muricata L.) Leaf Extract Inhibitor - Wulandari, Tsaniyah; Asdim, Asdim; Hafizah, Mas Ayu Elita (Indonesian Journal of Chemical Analysis (IJCA), 2023)
Exploration of soursop leaf extract (Annona muricata L.) as one of the natural inhibitors against the corrosion process. The objective of this research is to determine the effect of the extract on inhibiting the corrosion rate of steel. The corrosion rate is determined by the decrease in the mass of the steel during immersion in various concentrations of sulfuric acid solutions, namely 0.01, 0.05, and 0.1 M, and optical microscopy will be used to analyze the corroded steel samples. This study consists of several stages: soursop leaf extraction, steel sample preparation, inhibitor solution and corrosive media preparation, immersion, and characterization. The extraction method is performed by maceration for 168 hours to obtain the extract. The highest corrosion inhibition efficiency obtained is 63.1% with the presence of 600 ppm inhibitor in 0.01 M sulfuric acid solution, while the lowest corrosion inhibition efficiency obtained is 14.8% with the use of 200 ppm inhibitor in 0.1 M sulfuric acid solution. The types of corrosion that occur on the steel surface are uniform corrosion and pitting corrosion.